Templars as bankersl - Falus, Orsolya (Acta Scientiarum Socialium, 2013)
Templars as bankers The Knights Templar trace their origin back to shortly after the First Crusade. Their mission was to protect pilgrims on their journey to visit the Holy Land. Though initially an Order of poor monks, papal sanctions made the Knights Templar a charity across Europe. Further resources came in when members joined the Order. Additional revenue came from business dealings. Since the monks themselves were sworn to poverty, but had the strength of a large and trusted international infrastructure behind them, nobles would occasionally use them as a kind of bank or power of attorney. If a noble wished to join the Crusades, this might entail an absence of years from their home. So these nobles would place all of their wealth and businesses under the control of Templars, to safeguard it for them until their return. By 1150, the Order's original mission of guarding pilgrims had changed into a mission of guarding their valuables through an innovative way of issuing letters of credit, an early precursor of modern banking.
Keywords: monks; papal sanctions; bankers; guarding; letters of credit